LANGGAM ARSITEKTUR MASJID AGUNG DARUSSALAM PURBALINGGA - Fadhilah Siti Aniisah Haryono; Muhammad Nur Hakimuddin At-toyibi (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2026)
The Darussalam Grand Mosque in Purbalingga is a religious building that plays a significant role as a center of worship, social activities, and a visual marker of the urban area. This study aims to identify the elements that shape the architectural style and to formulate the dominant pattern tendencies in the existing building. The study uses a descriptive qualitative method with an architectural analysis approach based on visual observation. Data were obtained through field observations, documentation, recording of building elements, and literature searches. The analysis includes massing, facade, roof, dome, minaret, interior space, mihrab, pulpit, ornaments, colors, and materials. The results show that the architectural character of the mosque is formed through a combination of Islamic, Middle Eastern, local Nusantara, and modern elements. Islamic and Middle Eastern influences are evident in the dome, tall minaret, arched openings, calligraphy, geometric patterns, and arabesque ornaments. Local elements are present through the use of a tiered tajug roof and a carved wooden pulpit. Meanwhile, the modern character is seen in the open layout, neat wall planes, colored glass, natural lighting, and glossy materials. The symmetrical composition, monumental scale, and vertical accents of the minaret strengthen the building's image as a city marker. Thus, the Darussalam Purbalingga Grand Mosque has an acculturative architectural style, with Islamic-Middle Eastern elements as the dominant expression, local elements as context markers, and modern solutions as the language of building materials.